Manganese as a Micronutrient in Agriculture: Crop Requirement and Management (Journal of Environmental Science and Natural Resources, 2021)
Manganese (Mn) as an essential plant micronutrient affects plant development, when at deficient or toxic levels. Manganese is used in several biological processes as an important contributor in plant growth and development. Manganese uptake depends on forms of Mn in soil solution, crop characteristics including growth rate, and ineteractions with other environmental factors. Its distribution in soils and requirement for crops vary from location to location, depending on soil type and reactions. Despite the metabolic roles of Mn in different plant cell compartments, the importance of Mn requirement in plants, distribution in soils and application to crops has been understated. As a micronutrient, judicious Mn management requires to critically evaluating its concentration in soils, biochemical functions, critical levels, soil availability and interactions with other nutrient elements is essential. This review has critically analysed the existing body of knowledge on Mn distribution in soils, dynamics, functions and management towards better crop production and safe environment.Environ. Sci. & Natural Resources, 12(1&2): 225-242, 2019